Product versus Process: Innovation Strategies of Multi-Product Firms - Lisandra Flach; Michael Irlacher (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
This paper studies the innovation strategies of multi-product firms in industries with different scope for product differentiation. In a simple model of multi-product firms, we show that returns to product versus process innovation are industry-specific. Demand and cost linkages induce a natural distinction between the returns to product and process innovation. In highly differentiated industries, the cannibalization effect is lower and, therefore, firms invest more in product innovation. In homogeneous industries, firms internalize intra-firm spillover effects and invest more in process innovation. We test the predictions from the model using Brazilian firm-level data, with information on investment efforts over time. Following a major exchange rate devaluation, firms have better access to foreign markets and exploit economies of scale in innovation. However, detailed information on product and process innovation allows us to evaluate differential effects across industries. We con.rm the predictions from the theoretical model and show that the type of innovation depends on the industry scope for differentiation.
urn:nbn:de:bvb:19-epub-21022-6
Keywords: F12; F14; L25; 330; Multi-Product Firms; Innovation; Product Differentiation; Cannibalization Effect; Spillovers; Globalization